X-Parameter Measurement of Pulse-Compression Nonlinear Transmission Lines. (17th November 2009) - Li, Ming; Amaya, Rony E.; Harrison, Robert G.; Tarr, N. Garry
Abstract : X -parameters provide a powerful and eminently practical solution for interoperable measurement, modeling, and simulation of nonlinear microwave and RF components. UsingX -parameters to do large-signal measurements has been brought into the spotlight. This paper introduces a newX -parameter application: measuring large-signal behaviour of pulse-compression nonlinear transmission lines (NLTLs). A specially configured Nonlinear Vector Network Analyzer (NVNA) was used to measure theX -parameters in the frequency-domain, and then the measured data was transformed into a nonlinear time-domain waveform. The results show both rise-time and fall-time reduction (double-edge compression) as expected and indicate that this newly developedX -parameter method implemented with an NVNA could correctly predict NLTLs' pulse-compression performance.